Impact of Window-to-Wall Ratio on Heating Demand and Thermal Comfort When Considering a Variety of Occupant Behavior Profiles - Veillette, Debby; Rouleau, Jean; Gosselin, Louis (Frontiers in Sustainable Cities, 2021)
Energy consumption and thermal comfort in residential buildings are highly influenced by occupant behavior, which exhibits a high level of day-to-day and dwelling-to-dwelling variance. Although occupant behavior stochastic models have been developed in the past, building design is typically optimized with static “average” occupant behavior schedules which do not account for all possible profiles. In this work, we evaluate how window-to-wall ratio (WWR) of a residential unit affects performance when considering a high number of occupant behavior profiles. A stochastic occupant behavior model generates a high number of possible profiles, which are then used as input in an energy simulation of the dwelling. As a result, one obtains probability distributions of energy consumption and comfort for different building designs. The paper shows that the shape of the probability distributions is affected by WWR and orientation, and that the relative importance of the different occupant behavior aspects on performance also varies with WWR. This work could help designers to better assess the impact of WWR for a large spectrum of possible occupant behavior profiles.